Effects of cryptotanshinone in treatment of polycystic ovary syndrome in rats: a systematic review and meta-analysis - Su, Pingping; Wang, Xv; Cai, Ruoqian; Yan, Chang; Sun, Yun (Frontiers in Pharmacology, 2025)
BackgroundPCOS is a prevalent endocrine disorder characterized by metabolic dysfunctions, including insulin resistance and hyperandrogenism. Cryptotanshinone, a bioactive compound, has shown promise in addressing reproductive abnormalities. However, its therapeutic potential for the management of PCOS has not been sufficiently investigated.PurposeThe aim of this study is to systematically evaluate the therapeutic efficacy of cryptotanshinone in the treatment of PCOS.MethodsA comprehensive systematic search was performed across multiple databases, including CNKI, Wanfang Data, VIP, PubMed, and Web of Science, covering studies from their inception through December 2024. The methodological quality of the included studies was assessed using SYRCLE’s Risk of Bias tool. Data synthesis and statistical analysis were conducted using RevMan 5.3 and Stata 17 software.ResultsSeven studies met the inclusion criteria for meta-analysis. Treatment with cryptotanshinone significantly improved several PCOS-related parameters in animal models, as compared to the control group. Notable improvements included reductions in body weight (P < 0.00001), ovarian weight (P = 0.005), and ovaries quotiety (P = 0.0006). Additionally, cryptotanshinone treatment led to significant modulation of serum levels f T (P = 0.001), A2 (P = 0.02), LH (P = 0.0002), LH/FSH ratio (P = 0.001), estradiol (P = 0.005), and SHBG (P = 0.0003). The underlying mechanism may involve the downregulation of CYP17 and AR mRNA and protein expression.ConclusionThis meta-analysis provides robust evidence supporting the therapeutic efficacy of cryptotanshinone in PCOS. Cryptotanshinone appears to restore both reproductive and metabolic functions, including the regulation of body weight, ovarian morphology, hormone levels, and gene expression. Cryptotanshinone holds significant promise as a potential therapeutic agent for the management of PCOS.